PENGARUH PEMBERIAN TERAPI OKSIGEN DENGAN MENGGUNAKAN NON-REBREATHING MASK (NRM) TERHADAP NILAI TEKANAN PARSIAL CO2 (PaCO2) PADA PASIEN CEDERA KEPALA SEDANG (MODERATE HEAD INJURY) DI RUANG INTENSIVE CARE UNIT (ICU) RSUP H ADAM MALIK MEDAN TAHUN 2016 - Marlisa Marlisa (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2016)
Head injury is any cases that caused high disability and mortallity rate. In neurology, head injury occupies the first squence and become the main of health problem to most youth, health and productive peoples. The treatment of head injury treatment is to prevent damage of brain cells by adequate oxygenation. The objective of the research was to find out the influence of giving oxygent therapy by using non-rebreathing mask (NRM) towards changing of partial pressure CO2 (PaCO2) value to head injury patients in ICU room of H. Adam Malik Hospital Medan. The research used the quasi experiment method with time series design. The samples were 10 respondents, taken by purpossive sampling technique. The instrument of the research was observation sheet. The result of the research showed that before given the oxygent therapy by using nonrebreathing mask (NRM), 5 respondents (50%) had normal blood pH value, 6 respondents (60%) had low blood HCO3- value, and 6 respondents (60%) had normal blood PaCO2 value. After given oxygent therapy found that 5 respondents (50%) had low blood pH value, 6 respondents (60%) had low blood HCO3- value, and 7 respondents (70%) had low blood PaCO2 value. The result of statistic analyze with T-Test was found significant influence of changing PaCO2 value with p value = 0,000 (p<0,05). The reduction of PaCO2 value is followed by increasing of blood pH value and reduction of blood HCO3- value. Using of non-rebreathing mask (NRM) is only effective for head injury patients with high blood PaCO2.